VARIAÇÃO DIURNA ENTRE MATUTINOS E VESPERTINOS NOS TEMPOS DE REAÇÃO SIMPLES E DE MOVIMENTO - Cassio de Miranda Meira Jr.; Ana Amélia Benedito-Silva; Mariana Muriel Vitorio Falconi (Journal of Physical Education)
ABSTRACT The circadian rhythm of motor performance is synchronized to the body temperature rhythm, with highest values occurring in the afternoon, and to the sleep-wake cycle, with individual preferences of sleep-onset and wake-up times. The aim of this study was to determine whether differences between the preferences of hours of sleep and wake (morningness-eveningness) have an impact on reaction times (RT) and motion (TM) measured in the early morning and late afternoon. Forty students, 20 morning-types and 20 evening-types, performed by the morning and by the afternoon a key-pressing task with measures of simple reaction time and movement time. According to the results, both morning-types and evening-types showed lower simple reaction times in the afternoon as compared to values in the morning and morning-types obtained lower movement times than evening-types, both in the morning and in the afternoon. Thus, it can be concluded that morningness-eveningness influenced the movement time, but not the simple reaction time.